Air mass modification processes over the Balkans area detected by aerosol lidar techniques - Nicolae, Doina N.; Talianu, Camelia L.; Mamouri, Rodanthi-Elisavet (My University, 2008)
Anthropogenic aerosols may have a substantial effect on the present-day aerosol abundance, optical depth and thus, may play an important role on the forcing of climate. This study combines aerosol lidar measurements with atmospheric modeling in order to assess the origin and type of aerosols affecting air quality in the Balkans region, and thus, having an impact on a possible modification of regional radiative budget. Based on the climatological aerosol data set containing the spatial and temporal evolution of the vertical distribution of aerosols over Greece and Romania, derived from lidar measurements, an analysis of two case studies is presented: one evidencing smoke aerosols traveling over the Balkan area, and the second evidencing transport of Saharan dust particles.
Keywords: Aerosols; Remote sensing; Optical radar; Dust